University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 7 - Section 7.1 - The Logarithm Defined as an Integral - Exercises - Page 402: 47


$y(t)=-\cos (e^t-2) +1$

Work Step by Step

Given: $\dfrac{dy}{dt}=e^t \sin (e^t-2)$ Here, $y=\int e^t \sin (e^t-2) dt$ Plug $a=e^t-2 \implies da=e^t dt$ Now, we have $y=\int \sin a da$ or, $y=-\cos a da+c$ Thus, $y=-\cos (e^t-2 )+c$ Apply initial conditions $y[\ln (2)]=2$ Thus, we have $y(t)=-\cos (e^t-2) +1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.